Anti-Inflammatory Effects of Hyeonggaeyeongyo-tang: Evidence from In Vitro and In Vivo Studies - Keun Hee Lee; Min Hee Kim; Hae Jeong Nam (Life)
Hyeonggaeyeongyo-tang (HGYGT), a traditional herbal formula, is used to treat inflammatory otorhinolaryngological diseases such as otitis media and sinusitis. In this study, we investigated the anti-inflammatory effects of HGYGT in LPS-stimulated RAW 264.7 cells (in vitro) and a carrageenan (CA)-induced rat paw edema model (in vivo). In LPS-stimulated RAW 264.7 cells, treatment with HGYGT (100 and 300 μg/mL) significantly reduced nitric oxide (NO) production by 24.5% and 51.3%, respectively (p < 0.05, p < 0.01). It also significantly suppressed the production of PGE2 (49.8%), IL-1β (42.7%), IL-6 (45.6%), and TNF-α (47.2%) at 300 μg/mL (p < 0.01). A Western blot analysis confirmed that HGYGT (300 μg/mL) significantly downregulated iNOS and COX-2 expression by 58.4% and 53.1%, respectively, while COX-1 remained unaffected. And HGYGT treatment at 300 μg/mL markedly inhibited NF-κB activation by 44.9% (p < 0.01). Furthermore, HGYGT selectively inhibited JNK phosphorylation by 46.7% (p < 0.01), without significantly affecting ERK1/2 or p38 MAPKs. In the CA-induced rat paw edema model, oral administration of HGYGT (1.0 g/kg) reduced paw swelling by 31.5% at 4 h post-injection (p < 0.01) and significantly decreased iNOS expression in inflamed paw tissues by 43.2% (p < 0.01). A histological analysis revealed that HGYGT (1.0 g/kg) reduced inflammatory cell infiltration by 39.6% in the affected tissue (p < 0.05), demonstrating its anti-inflammatory potential. Our findings demonstrate that HGYGT exerts anti-inflammatory effects by suppressing the JNK and NF-κB signaling pathways in LPS-stimulated RAW 264.7 cells, reducing the production of inflammatory mediators. Notably, HGYGT selectively inhibits COX-2 without affecting COX-1 and preferentially suppresses the JNK pathway. Moreover, its in vivo anti-inflammatory effects were confirmed through iNOS inhibition and histopathological analysis. These findings provide robust scientific evidence supporting the traditional use of HGYGT and its anti-inflammatory properties.